HLA‐DQA1*03:03:01:16Q, a novel allele with an acceptor splice site mutation. (26th August 2021) - Casey, Heather; Tyler, Jennifer; Fisher, Carolyn; Mowery, Carrie; Shike, Hiroko
Abstract : DQA1*03:03:01:16Q differs from DQA1*03:03:01:01 by one nucleotide at the Intron 3 splicing acceptor site.